Disrespect and abuse during facility‐based childbirth in central Ethiopia - Yohannes Mehretie Adinew; Helen Hall; Amy Marshall; Janet Kelly (Global Health Action)
Background Respectful maternity care is a fundamental human right, and an important component of quality maternity care. Objective The aim of this study was to quantify the frequency and categories of D&A and identify factors associated with reporting D&A among women in north Showa zone of Ethiopia. Method A cross-sectional study was conducted with 435 randomly selected women who had given birth at public health facility within the previous 12 months in North Showa zone of Ethiopia. A digital (tablet-based) structured and researcher administered tool was used for data collection. Frequencies of D&A items organised around the Bowser and Hill categories of D&A and presented in the White Ribbon Alliance’s Universal Rights of Childbearing Women Framework were calculated. Multivariable logistic regression was used to identify the association between experience of disrespect and abuse and interpersonal and structural factors at p-value <0.05 and odds ratio values with 95% conﬁdence interval. Results All participants reported at least one form of disrespect and abuse during childbirth. Types of disrespect and abuse experienced by participants were physical abuse 435 (100%), non-consented care 423 (97.2%), non-confidential care 288 (66.2%), abandonment/neglect (34.7%), non-dignified care 126 (29%), discriminatory care 99 (22.8%) and detention 24 (5.5%). Hospital birth [AOR: 3.04, 95% CI: 1.75, 5.27], rural residence [AOR: 1.44, 95% CI: 0.76, 2.71], monthly household income less than 1,644 Birr (USD 57) [AOR: 2.26, 95% CI: 1.20, 4.26], being attended by female providers [AOR: 1.74, 95% CI: 1.06, 2.86] and midwifery nurses [AOR: 2.23, 95% CI: 1.13, 4.39] showed positive association with experience of disrespect and abuse. Conclusion Hospital birth showed consistent association with all forms of disrespect and abuse. Expanding the size and skill mix of professionals in the hospitals, sensitizing providers consequences of disrespect and abuse could promote dignified and respectful care.